Quo vadis, productivity? - Andreas Breitenfellner; Robert Holzmann; Richard Sellner; Maria Antoinette Silgoner; Thomas Zörner (Oesterreichische Nationalbank (OeNB), 2022)
Achieving high productivity growth is a central goal of policymaking, given that productivity (growth) impacts not only key macroeconomic variables, but also a country's living standards. Central banks have an intrinsic interest in promoting productivity growth because of its interaction with the natural rate of interest r*, a key variable of monetary policy. The natural rate of interest is also crucial for the scope of monetary policy space - both in terms of conventional and unconventional policies. Summarizing recent empirical evidence, we present nine hypotheses about why productivity dynamics may have slowed down recently in industrial countries around the world: (1) lack of (investment) demand; (2) expansionary monetary policy; (3) firm size and age; (4) technological cycles, the nature of recent innovations and the time it takes to apply them productively; (5) weak technological diffusion; (6) subdued creative destruction; (7) financial market dynamics and valuation; (8) population aging; and (9) regulation and the compliance burden. The factors that will shape future productivity trends may differ from today's and past drivers. For this reason, we highlight three policy fields that may become even more critical over the next decades: population aging, digitalization and climate change. We conclude that weak productivity growth must be approached from various angles. Appropriate policy mixes may differ widely across global and European regions. Here, central banks can play a crucial role in helping governments find this appropriate policy mix.
Keywords: 330